Sustainability for healthcare management : a leadership imperative - Rich, Carrie R.; Singleton, J. Knox; Wadhwa, Seema S. (Routledge, 2018)
"Sustainability is not unique to health, yet sustainability is a unique vehicle for promoting healthy values. This book challenges healthcare leaders to think through the implications of our decisions from fiscal, societal and environmental perspectives. It links health values with sustainability drivers in order to enlighten leadership about the value of sustainability as we move toward a new paradigm of health. Fully updated for the second edition, the book now includes case studies about:Waste disposal and costChemicals of concernCost of waterGreen building ratingsThis book is a unique resource for researchers, students and professionals working in health and healthcare management because the book connects key concepts of environmental sustainability with healthcare operations. Readers will gain an appreciation for translating leadership priorities into sustainability tactics with beneficial operational outcomes."--Provided by publisher.